“Efecto de mezclas probióticas en dieta sobre la respuesta productiva y química sanguínea en juveniles de vieja colorada (cichlasoma festae)” - Mesías Loor, Carlos Kelvin (2021)
The purpose of the study was to evaluate the effect of probiotic mixtures in the diet on the productive response and blood chemistry of juvenile old redband (C. festae) during the juvenile stage in a controlled system. The probiotic mixtures were fed to the fish diet according to a three-level formulation for a period of 60 days, and then a statistical analysis was applied to the data using a completely randomized design (ANOVA) and Tukey's multiple range test. The results obtained varied according to the proportion of probiotics supplied to the diet (0, 1, 3 %) granting the best response in most of the zootechnical parameters to 3% probiotics: 5.93 2.19 (final weight), 9.55 33.93 (TCE), 3.92 2.70 (TCA), ,42 0.92 (condition factor), 96.54 2.34 (survival rate), 2.15 1.49 (weight gain). In the nutritional parameters, no significant differences were observed between treatments; however, treatment T2 (0.4 ml of probiotic inclusion) obtained the most representative values for feed efficiency and feed conversion rate. In the case of blood chemistry parameters, there was a representative increase in the variables cholesterol and triglyceride with respect to the inclusion of probiotics at 0.2 ml (T1) and 0.4 ml (T2), while glucose was more outstanding in the T0 treatment (without probiotic inclusion). The physicochemical parameters of water quality: pH, ammonium and nitrite remain stable, and are suitable for C. festae culture environments, unlike nitrate and total hardness which were more abundant. Key words: triglycerides, cholesterol, blood plasma, diet, survival.